The Effect Of Tax Awareness, Tax Sanctions And Quality Of Services On Taxpayer Compliance In Paying For Motor Vehicles In Tangerang District - wulan safitri; Imam Hidayat (Jurnal Riset Perpajakan: Amnesty, 2022)
The purpose of this study is to analyze the influence of taxpayer awareness, tax sanctions and quality of service on taxpayer compliance in paying for motor vehicles in 2021. The method used is a quantitative method with primary data obtained from the dissemination of questionnaires, the sample in this research is a taxpayer in the SAMSAT Balaraja area of Tangerang Regency by using a sampling technique that is random sampling, the data analysis technique used is multiple linear regression. The results of this study showed that partially the variables of taxpayer awareness had a positive and significant effect, while the variables of tax sanctions and quality of service had a positive but insignificant effect. Meanwhile, simultaneously variable free taxpayer awareness, tax sanctions, and quality of service together have a significant relationship to the variables tied to it, namely taxpayer compliance